Novel 1 beta-Methylcarbapenems Having Cyclic Sulfonamide Moieties: Synthesis and Evaluation of in-vitro Biological Activity - Part II - Kim, Seong Jong; Cho, Jung-Hyuck; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2009)
The synthesis of a new series of 1 beta-methylcarbapenems having cyclic sulfonamide moieties is described. Their in-vitro antibacterial activities against both Gram-positive and Gram-negative bacteria were tested and the effect of a substituent on the pyrrolidine ring was investigated. One particular compound IIIe having a [1,2,5]thiadiazolidin 1,1-dioxide moiety showed the most potent antibacterial activity.
Keywords: BETA-LACTAM ANTIBIOTICS; ANTIBACTERIAL ACTIVITY; CARBAPENEMS; DERIVATIVES